Behaviour of circular sandwich panel under dynamic loading - Alias, Amran; Mat Rejab, Mohd. Ruzaimi; Mohamad, Mohd. Radzai; Md. Akil, Hazizan; Ahmad Nor, Nor Azlan (Faculty of Mechanical Engineering, 2005)
In this paper, the dynamic tests were conducted in order to determine the performance, mechanical behaviour, effect of foam type and the correlation between input energy from static and dynamic tests. Emphasis is placed on assessing the failure modes occurred after the dynamic test and the comparison is made with the static test. Same type of failure behaviours were observed for the circular sandwich panels with different PU and R55 foam cores. The load versus displacement diagrams show that dynamic loading requires more input energy to create the same type of failure than that of static loading for circular PU sandwich panels. For circular R55 sandwich panels, it behaves oppositely, where higher loads were recorded in the static cases.